2000
DOI: 10.1038/sj.bmt.1702675
|View full text |Cite
|
Sign up to set email alerts
|

No effect of nadroparin prophylaxis in the prevention of central venous catheter (CVC)-associated thrombosis in bone marrow transplant recipients

Abstract: Summary:Complications of CVCs in 382 consecutive patients receiving a stem cell transplantation (SCT) were analysed. Early complications were pneumothorax (3.6%), haematothorax (0.5%), dislocation (3%) and dysfunction (3.6%). Eighty-seven-associated infections (22%) were observed, leading to removal of the CVC in 26 patients. More bacteraemias were associated with double-or triple-lumen CVCs, 19% vs 5% in single lumen CVCs (P Ͻ 0.0001). Coagulase-negative staphylococci were the predominant microorganisms in 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…Recently, Mismetti et al have shown that LMWH and low doses of warfarin are as efficient in the prevention of CRT [20]. However, shorter courses of LMHW (7 to 10 days or 30 days) have not been proven to be effective in preventing CRT [16,19].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Mismetti et al have shown that LMWH and low doses of warfarin are as efficient in the prevention of CRT [20]. However, shorter courses of LMHW (7 to 10 days or 30 days) have not been proven to be effective in preventing CRT [16,19].…”
Section: Discussionmentioning
confidence: 98%
“…In a retrospective study, Lagro et al found nadroparin to be ineffective in the prevention of CVCrelated thrombosis in bone-marrow transplant recipients [17]. The occurrence of thrombosis was 17 out of 221 (8%) in patients taking prophylaxis compared to 10 out of 161 (6%) patients receiving no prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…All catheters were flushed with 7 ml UFH (100 IU/ml) daily as well as after blood was drawn or drugs/blood products were administered. The thromboses were observed only after 22 days (median) and between day 5 and day 92, respectively (Lagro et al 2000). Attention should thus be paid to the longer-term assurance of effective prophylaxis of port catheter-associated thromboses.…”
Section: Discussionmentioning
confidence: 95%